Sistem Pakar Midiagnosa Penyakit Pelagra Menerapkan Metode Hybrid Case Based - Hapipuddin Hapipuddin; Muhammad Syahrizal (Journal of Information System Research (JOSH), 2020)
Expert system as a system that adopts human flapping into computers has a strategic position as a system that can help solve problems in the medical field. Difficult to determine the type of disease because of the complexity of the various symptoms that accompany it, can be helped by representing the symptoms of a disease into a computer programming language. In this study, a method was developed to diagnose pelagra based on the types of symptoms that accompany it. This expert system development environment uses the MySQL database.